Nutritional supplements for strength trained athletes - Williams, M. H. (1993)
1. For the strength-trained athlete attempting to increase muscle mass, probably the most important nutritional considerations are to obtain sufficient energy and protein. Adequate amounts of both may be obtained simply by increasing the amount of complex carbohydrates and healthful protein sources in the daily diet. 2. Most of the commercial nutritional products marketed for strength-trained athletes are promoted as a dietary means to influence metabolic processes that stimulate muscle growth and/or facilitate the loss of body fat, primarily by inducing the endogenous production or release of testosterone or human growth hormone (HGH). 3. There is little or no scientific evidence supporting positive effects on muscle growth, body fat reduction, or strength enhancement in strength-trained athletes for the following nutritional supplements: arginine, lysine, and ornithine (amino acids); ornitine alpha-ketoglutarate (OKG); ino-sine; choline; yohimbine; "glandulars;" vitamin B 12; carnitine; chromium; boron; magnesium; medium chain triglycerides; omega-3 fatty acids; gamma oryzanol; Smilax. Additional research is needed to support or refute claims made for some of these products, as well as others that may be of interest to strength-trained athletes, e.g., creatine and antioxidant vitamins. 4. Given the fraudulent claims made for most nutritional supplements marketed for strength-trained athletes, and because many are relatively expensive, let the buyer beware!